2005
DOI: 10.7863/jum.2005.24.10.1403
|View full text |Cite
|
Sign up to set email alerts
|

Epidermoid Cyst and Teratoma of the Testis

Abstract: There is considerable overlapping of the sonographic appearances of teratomas and epidermoid cysts of the testis. Although the onion ring appearance of an intratesticular tumor is suggestive of an epidermoid cyst, this appearance may also be found in cases of a teratoma. Whereas the former condition can be treated by local enucleation, the latter requires radical orchiectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…They usually occur in the hair-bearing areas of the body, such as the scalp, face, neck, trunk, and back [ 1 2 3 ]. Epidermal cysts are a rare benign tumor of the testicle, and are usually discovered in the second and fourth decades of life [ 4 ]. We report an unusual testicular mass in an older patient, in whom the testis was found to have been completely replaced with an epidermal cyst.…”
mentioning
confidence: 99%
“…They usually occur in the hair-bearing areas of the body, such as the scalp, face, neck, trunk, and back [ 1 2 3 ]. Epidermal cysts are a rare benign tumor of the testicle, and are usually discovered in the second and fourth decades of life [ 4 ]. We report an unusual testicular mass in an older patient, in whom the testis was found to have been completely replaced with an epidermal cyst.…”
mentioning
confidence: 99%
“…Alternatively, many cases of TEC show a heterogeneous echotexture with a target or bull's eye pattern consisting of a hyperechoic capsule, hypoechoic content of fat and water, and a hyperechoic central focus representing keratin debris. [8] It is uncommon to see calcifications. [4] Color Doppler examination consistently reveals TEC to be avascular,[312] unlike most testicular malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…[8] The latter histologic finding removes the tumor from the clearly benign category and necessitates aggressive treatment. In addition, TEC occasionally appears atypical, with a multilocular configuration, without the onion ring or target appearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, extensive keratinization inside the cyst makes a characteristic onion skin-like appearance, seen in ultrasound scan and magnetic resonance imaging (MRI) studies, which strongly supports the diagnosis [4]. However, recently it has been shown that mature teratomas might have a similar ultrasonic feature to the epidermoid cysts [5]. Therefore, though a triad of findings including the sonographic appearance of an onion ring, avascularity on Doppler sonography, and negative results of tumor marker studies-is highly suggestive of an epidermoid cyst, due to the above-mentioned it would be unsafe to completely rely on ultrasound [6].…”
Section: Discussionmentioning
confidence: 99%